PERILAKU DAN KARAKTERISTIK KONSUMEN DALAM MEMBELI SAYURAN PADA PASAR MODERN (GIANT SUPERMARKET) DI KOTA MAKASSAR - Jurnal Agribis; Sumarni B (Jurnal Agribis, 2019)
This research aims to determine the characteristics and behavior of consumers in buying vegetables at the Modern Market (Giant Supermarket) Alauddin Makassar. The method used in this research is a purposive sampling method, with as many as 30 respondents considering that not all respondents are willing to be interviewed. Qualitative analysis is used in this research. The results showed that the characteristics of consumers in buying vegetables at the Modern Market (Giant Supermarket) of Alauddin Makassar were dominated by women aged 31-40 years with an average education level as Bachelor and working as both civil servants and housewives with an income of Rp. 3,000,000-Rp. 5,000,000 per month with a married status and an average family member of 3-4 people with an expenditure of Rp. 300,000-Rp.400,000 to buy vegetables per month. Whereas consumer behavior in shopping vegetables was after seeing information from various sources and because they know that vegetables are important for body health, so they chose to shop at Giant because of its location is close to the respondent's residence, strategic, comfortable, and guaranteed cleanliness so that respondents felt very satisfied. On average, the respondents buy vegetables as much as 7-9 times per month or depending on the situation and their needs. The types of vegetables that are highest in demand are leafy vegetables.